Emissive mononuclear Eu(III) and Tb(III) complexes bearing deprotonated 2, 2′-bipyridyl-1, 2, 4-triazole terdentate ligands. Issue 19 (1st October 2016) - Chen, Jing-Lin; Gao, Guo-Ping; Di, Bao-Sheng; Luo, Yan-Sheng; Zeng, Xue-Hua; Qiu, Lu; He, Li-Hua; Liu, Sui-Jun; Wen, He-Rui
Abstract: A series of new emissive mononuclear Ln(III) complexes with deprotonated 2, 2ʹ-bipyridyl-1, 2, 4-triazole terdentate ligands, [Ln(L)(DMF)2 (NO3 )2 ]∙n(solvent) (Ln = Eu (1 and2 ), Tb (3 and4 ), HL = 6-(5-trifluoromethyl-1, 2, 4-triazol-3-yl)-2, 2′-bipyridine, 6-(5-trifluoromethyl-1, 2, 4-triazol-3-yl)-4, 4′-dimethyl-2, 2′-bipyridine), have been synthesized and characterized. As revealed by X-ray crystallography, each Ln(III) has a distorted tricapped trigonal prism generated by three nitrogens from one 2, 2ʹ-bipyridyl-1, 2, 4-triazolate chelate and six oxygens from two DMF molecules and two chelating nitrates, where 2, 2ʹ-bipyridyl-1, 2, 4-triazole serves as a mono-anionic tridentate chelate via deprotonation of the 1, 2, 4-triazolyl-NH. Complexes1 –4 are all emissive at room temperature in solution and solid states, and the introduction of two methyl groups into the 2, 2ʹ-bipyridyl ring is efficient in enhancing luminescence efficiencies of Ln(III) complexes. Abstract :